"Asthma is a very bully disease" - patient experiences of living with chronic respiratory diseases in Cape Town, South Africa - Marie Stolbrink; Chantel Streicher; Khanyisa Mcimeli; Brian Allwood; Kevin Mortimer; Martha Chinouya (BMC, 2023)
Abstract Background Chronic respiratory diseases are common in Cape Town, South Africa. Yet the experiences of how adults with these conditions, such as asthma or COPD (chronic obstructive pulmonary disease), negotiate the health system are poorly understood. Qualitative methodology lends itself to investigate this question. Aim of study To explore the "emic" experiences of adults with CRDs in Cape Town when they were negotiating the health system using semi-structured interviews. Methods Interviews were conducted following informed consent with purposively sampled adults who had attended public hospitals in Cape Town with chronic respiratory disease flare-ups. This work was nested in the quantitative "Diagnosing Airways Disease" study. The topic guide explored patients' experiences of accessing healthcare including receiving and interpretations of the diagnosis and management, and impacts on daily life. Interviews were conducted in Afrikaans, isiXhosa, or English; transcribed, and translated into English and thematically analysed until saturation. Results Thirty-two interviews (16 in Afrikaans, 8 in isiXhosa, 8 in English) were completed in 2022. 17 women and 15 men participated. Most participants were older than 50 years (25/32), and most were unemployed (13/32) or retired (11/32). The identified themes were: Perceived causes of illness; experiences of healthcare; perceived risks and barriers when accessing healthcare; and impact on earnings. The perceived causes of their illness and risks were structural, and included air pollution, poor quality housing, occupational exposures, limited healthcare services, and fear of violence. These factors led to self-treatment, sharing of medicines, and delay in receiving a diagnosis. Many paid privately for treatments or services to overcome identified shortcomings of the public healthcare system, and many reported additional significant indirect costs. Being ill had a profound impact on income. The identified themes were explored through the lens of "structural violence", where "social structures stop individuals ... from reaching their full potential" (Galtung, 1969). Conclusion In Cape Town structural elements such as stretched healthcare professionals, insufficiently enforced policies on e.g., housing or work-place exposures, poverty and crime made it difficult for participants to successfully navigate their illness experience. It forced some to pay out of pocket to receive perceived better healthcare privately.